2019
DOI: 10.1002/ijc.32185
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of luminal breast cancer reveals a role for LOL in tumor progression and tamoxifen resistance

Abstract: Luminal breast cancer (BC) has a sustained risk of late disease recurrence and death. Considerable numbers of patients suffer from antiendocrine therapy resistance. Here, we identified a novel lncRNA whose expression is high in breast cancer and especially higher in luminal breast cancer, dubbed LOL (lncRNA of luminal), that acts as a natural sponge for let‐7 microRNAs to regulate tumor growth and tamoxifen resistance. LOL overexpression in parental MCF‐7 cells exhibited a proliferative advantage in the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…However, these markers focused on TNBC or distant metastasis. [6][7][8][10][11][12][13] Recent studies have revealed that lncRNAs played vital roles in the development of cancers. 21,22 Further, germline mutations can also predict tumor recurrence in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these markers focused on TNBC or distant metastasis. [6][7][8][10][11][12][13] Recent studies have revealed that lncRNAs played vital roles in the development of cancers. 21,22 Further, germline mutations can also predict tumor recurrence in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the identification of prognostic markers, which can be potential targets, is of importance. Recently, genes or proteins were proved to be an oncogene role or promoting metastasis in the luminal subtype, [10][11][12][13] while little were verified to be related to overall survival (OS). Moreover, most of them were genomic, along with some microRNAs (miRNA), while Long non-coding RNAs (lncRNA) were rarely mentioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…JQ1 attenuated proliferation of tamoxifen-resistant ER + cells at a greater extent comparing to parental cells, by reducing BRD3/4 recruitment to ERa promoter [ 32 ]. In addition to this, ENST00000456526 is a long noncoding RNA, namely LOL (lncRNA of luminal), which is overexpressed in luminal breast cancer [ 65 ]. ER + tamoxifen-resistant cells demonstrate a higher LOL expression compared to parental cells.…”
Section: Combination Treatment and Resistancementioning
confidence: 99%
“…Knockdown of LOL reverses TAM resistance in TamR MCF-7 cells by sponging let-7 miRNAs. 82 LncRNA DSCAM-AS1 promotes TAM resistance via the miR-137/EPS8 axis or by modulating GREB1, a target of ER. It promotes cell reproduction and suppresses cell apoptosis by acting as a ceRNA of miR-137 and increasing EPS8 expression.…”
Section: Tamoxifenmentioning
confidence: 99%